TENDENCY OF FRAUDULENT BEHAVIOR IN REGIONAL FINANCIAL AND ASSET MANAGEMENT (STUDY AT THE REGIONAL FINANCE AND ASSETS AGENCY OF WEST BANDUNG REGENCY) - Nur’aeni, Feni; Afriady, Arif (Accounting Department, Politeknik Negeri Bandung, 2023)
This study aims to determine the effect of fraud hexagon theory on the tendency of fraudulent behavior in regional financial and asset management in West Bandung Regency. This study used quantitative methods with 40 samples from the employees of the Regional Finance and Asset Agency of West Bandung Regency. The data used was primary data with questionnaire techniques using a likert scale. The hypothesis was tested using multiple linear regression analysis method that is carried out by the SPSS software version 23. The results showed that Stimulus (Financial Pressure), Capability (Competence), and Collusion had a significant positive effect on the tendency of fraud in regional financial and asset management. Conversely, Opportunity (SPIP Effectiveness), Rationalization (Organizational Culture) and Ego (Morality) have a significant negative effect on the tendency of fraudulent management of regional finances and assets. The variables of (Financial Pressure), Capability (Competence), Collusion, Opportunity (SPIP Effectiveness), Rationalization (Organizational Culture) and Ego (Morality) simultaneously affect the tendency of fraud in regional financial and asset management.